2009
DOI: 10.1534/genetics.109.105601
|View full text |Cite
|
Sign up to set email alerts
|

curledEncodes the Drosophila Homolog of the Vertebrate Circadian Deadenylase Nocturnin

Abstract: Drosophila melanogaster curled, one of the first fly mutants described by T. H. Morgan .90 years ago, is the founding member of a series of curled wing phenotype mutants widely used as markers in fruit fly genetics. The expressivity of the wing phenotype is environmentally modulated, suggesting that the mutation affects the metabolic status of cells rather than a developmental control gene. However, the molecular identity of any of the curled wing marker mutant genes is still unknown. In a screen for starvatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 76 publications
0
38
0
1
Order By: Relevance
“…We used our dual gRNA plasmid to make a transgenic line simultaneously expressing gRNAs targeting e or curled (cu), which causes a curled wing phenotype when mutated (23), and crossing that line to act-cas9 flies. All 120 of the analyzed act-cas9 gRNA-e gRNA-cu flies had large patches of dark cuticle, and 52% had one or two curled wings (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used our dual gRNA plasmid to make a transgenic line simultaneously expressing gRNAs targeting e or curled (cu), which causes a curled wing phenotype when mutated (23), and crossing that line to act-cas9 flies. All 120 of the analyzed act-cas9 gRNA-e gRNA-cu flies had large patches of dark cuticle, and 52% had one or two curled wings (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Disrupting cu or HR4 function via RNAi in the RG or the PG reduced the duration of larval development in both genotypes by 10 (Figure 4D) or 7 hr (data not shown), respectively. Drosophila CU is orthologous to vertebrate Nocturnin (NOC), a circadian rhythm effector protein (Grönke et al, 2009). Interestingly, NOC interacts with the nuclear receptor PPARγ to facilitate its translocation to the nucleus, raising the possibility that a similar interaction may occur between CU and HR4.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to CCR4, encoded by the gene twin, the Drosophila genome also encodes three paralogs: Angel, Nocturnin (encoded by curled) (Grönke et al 2009), and 3635. Reverse transcription-polymerase chain reaction (RT-PCR) analysis showed that twin, angel, and 3635 are expressed in S2 cells, but curled is not (data not shown).…”
Section: Association Of Nocturnin With the Ccr4-not Complexmentioning
confidence: 99%